Acute Coronary Syndrome in the Context of Normal Cardiac Troponin Level- A Case Report - Islam, Tarekul; Antor, Mohammed Rifat Hasan; Alam, Shafiqul; Qumruzzaman, Kh; Bari, Ahmed Saiful; Abdullah, Abu Sadique; Osmany, DMMF; Safiuddin, Mohammad (University Heart Journal, 2025)
Acute coronary syndrome (ACS), counted globally as the leading cause of mortality in recent times. Typical clinical presentation of ACS is due to a mismatch between the supply and demand of oxygen (O2) which leads to cardiac ischemia and necrosis. Troponin I, A serum biomarker of myocardial injury has a 99% sensitivity rate in identifying the myocardial damage, and very few instances may deviate from this norm. We report a rare case of ACS where repeated testing of troponin levels returned negative results, even after tests conducted at three different laboratories. University Heart Journal 2025; 21(1): 53-57